DNMT1 and EZH2 mediated methylation silences the microRNA-200b/a/429 gene and promotes tumor progression. Issue 2 (10th April 2015) - Ning, Xianghong; Shi, Zhendong; Liu, Xi; Zhang, Anling; Han, Lei; Jiang, Kui; Kang, Chunsheng; Zhang, Qingyu
Highlights EZH2 regulates the tri-methylation of H3K27 and reduces DNMT1 expression. Knocking-down of DNMT1 down-regulates the components of the PRC2 (EZH2, SUZ12, EED) complex. EZH2 and DNMT1 inactivate the expression of mir-200b/a/429 cluster.